Teoria efektów stratyfikacyjnych Raymonda Boudona i jej współczesne implementacje w badaniach edukacyjnych. - Długosz, Piotr (Studia Edukacyjne, 2020)
The aim of the article is to apply Raymond Boudon’s theory of educational inequalities to the analysis and explanation of educational inequalities in Poland. The theory of primary and secondary effects of stratification was tested among the groups of middle school students (N = 1787) and secondary school leavers (N = 1168). The results of the analyses in both groups confirmed the presence of all the mechanisms of educational inequalities formulated within Boudon’s theory. First of all, the influence of one’s standing and capitals on the attitude towards education was observed. The students from middle classes more often valued tertiary education highly and noticed the relationship between higher education and life success. Secondly, educational performance was higher among the students of higher status, equipped with capitals. Thirdly, in the case of identical educational achievements, more ambitious educational choices were made by students of higher status. Fourthly, the influence of middle schools on educational aspirations has been discovered. The results of the research confirmed the validity of the theory of effects of stratification and proved its relevance and usefulness in terms of researching the effects of educational changes in Poland.